2020
DOI: 10.3390/curroncol28010014
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Metastatic Testicular Cancer

Abstract: We investigated the prognostic utility of pre-chemotherapy neutrophil-to-lymphocyte ratio (NLR) in patients with metastatic germ cell tumors (GCTs) undergoing first-line chemotherapy. We utilized two institutional databases to analyze the pretreatment-derived NLR (dNLR). Predictive accuracy was evaluated using the Cox proportional hazard model adjusted for the international germ cell cancer collaborative group (IGCCCG) risk classification. Discriminatory accuracy was evaluated by determining the area under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
3
14
0
3
Order By: Relevance
“…In addition, survival analyses revealed that the percentage of neutrophils and lymphocytes could be used as a prognostic factor for PFS and OS, but not independently of the IGCCCG classification, in an analyzed cohort of chemotherapy-naïve GCT patients. Similar findings were also presented by Ribnikar et al (27).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, survival analyses revealed that the percentage of neutrophils and lymphocytes could be used as a prognostic factor for PFS and OS, but not independently of the IGCCCG classification, in an analyzed cohort of chemotherapy-naïve GCT patients. Similar findings were also presented by Ribnikar et al (27).…”
Section: Discussionsupporting
confidence: 92%
“…It is interesting to note that the increased levels of cytotoxic T cells were described in patients with poor prognosis according to the IGCCCG classification, and the presence of lung and non-pulmonary visceral metastases. These results also support the implication of the pro-inflammatory state noted in the tumor burden, which was supported by the interconnection between high neutrophil percentage and decreased percentage of lymphocytes and activated T cells ( 27 , 45 – 47 ). In addition, survival analyses revealed that the percentage of neutrophils and lymphocytes could be used as a prognostic factor for PFS and OS, but not independently of the IGCCCG classification, in an analyzed cohort of chemotherapy-naïve GCT patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A similar finding also reported a correlation between high NLR value and low chemotherapy response rate (Karakaya et al 2021). Survival parameters were reported that NLR was associated with progression-free survival (PFS) and overall survival (OS) (Ribnikar et al 2021). Even though this study showed that NLR seemed to be higher in patients with stable and progressive disease than patients with partial and complete response, a definitive conclusion still could not be made until a prospective cohort prognostic study with larger sample size is performed.…”
Section: Discussionmentioning
confidence: 59%
“…Among these biomarkers, dNLR is a popular and novel biomarker that measures the immunity or inflammation ratio in cancers. Increasing evidence has shown that high dNLR is significantly associated with poor prognosis in several types of cancers, including ESCC, NSCLC, non-colorectal gastrointestinal cancer, prostate cancer, melanoma, testicular cancer, and ampullary cancer [ [15] , [16] , [17] , [18] , [32] , [33] , [34] ]. It is encouraging that these studies were consistent with our results.…”
Section: Discussionmentioning
confidence: 99%